Lessons learned: risk factors and clinical impact of severe pneumothorax after endoscopic lung volume reduction with endobronchial valves - Brock, Judith; Dittrich, A. Susanne; Eichhorn, Florian; Schlamp, Kai; Kontogianni, Konstantina; Herth, Felix (Chest, 2025)
Background - Pneumothorax is a major complication after endoscopic lung volume reduction with valves, with a prevalence of up to 34%. Although some patients benefit from valve implantation despite pneumothorax, others are significantly impaired after lung collapse. - Research Question - What are the differences in the severity grades of pneumothorax and how do these affect clinical practice? - Study Design And Methods - This single-center retrospective study analyzed patients undergoing endoscopic valve implantation with and without pneumothorax after intervention. Emphysema characteristics, collateral ventilation, management, and outcome of patients with pneumothorax 3 months after valve implantation were assessed. Pneumothorax was categorized as severe (chest tube insertion, prolonged air leak requiring valve removal), moderate (chest tube, no valve removal), and mild (no chest tube). - Results - Pneumothorax occurred in 102 of 532 patients (19%) and was significantly more common after valve placement in the upper lobes (31.3%) compared with the lower lobes (11.3%; P < .001). Fissure integrity was significantly higher in patients with pneumothorax (mean, 96.6 ± 6.3% vs 93.4 ± 10.3%; P = .002). Of all pneumothoraces, 30.4% were mild, 30.4% were moderate, and 39.2% were severe. Severe pneumothorax caused multiple complications and prolonged hospitalization. Valve placement in the left upper lobe and a larger size of the target lobe were identified as risk factors for severe pneumothorax. Patients with pneumothorax demonstrated complete lobar atelectasis in > 60% as a sign of therapeutic success, but obviously only when valves could be left in place or reimplanted. However, valve reimplantation resulted in repeat pneumothorax in 42.9%. - Interpretation - Patients could be informed more individually about their risk of pneumothorax, which varies with target lobe location, fissure integrity, and reimplantation. The poor outcome and high complication rate of severe pneumothorax calls for future research into the prediction of severe pneumothorax.